Hubungan Penggunaan Media Promosi Kesehatan Dengan (Audiovisual) Tentang Praktik Cuci Tangan Pada Anak TK Wulele Sanggula Abeli Di Wilayah Abeli Tahun 2023 - Rahmaniar Rahmaniar; Hartati Bahar; Kamrin Kamrin (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The aim of this research is to assess the impact of using audiovisual media on the knowledge, attitudes, and handwashing practices among preschool children at Wulele Sanggula Abeli Kindergarten in the Abeli Region in 2023. The research method employs a quantitative approach with a Pre-Experimental design and a one-group pretest-posttest design. The research sample consists of 40 children selected using total sampling technique. Research instruments include questionnaires and audiovisual media. The results indicate a significant improvement in knowledge (pre-test: 3.07; Post-test: 10.00), attitudes (pre-test: 3.15; Post-test: 10.00), and handwashing practices (pre-test: 2.30; Post-test: 6.00). It can be concluded that the use of audiovisual media has a positive influence on the knowledge, attitudes, and handwashing practices among preschool children at Wulele Sanggula Abeli, with important implications for improving hygiene and health habits in the school environment.